GO/rGO as Strengthening Nanofiller in Carbon Fiber/Epoxy Resin Composite Materials - Gemma Sanjuan Gomez; Manuel J Lis; Jiahui Li; Paul Coldea; Cristian Lopez De Prada; Jorge Fernandez Vela; Guido Ruffini Fores (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
Epoxy polymer composites with carbon fiber as reinforcement have an extensive range of applications in many industrial fields as: wind turbines, construction, aeronautics and aerospace due to their favorable strength-to-weight and stiffness-to-weight ratios, as well as their high thermal stability and excellent corrosion resistance. Interfacial interactions between matrix and composite reinforcement greatly influence the material’s final properties. Carbon Fibers are characterized as having low interactions with resins when forming a composite material. In the present study, 0.3 wt% of GO/rGO were incorporated in three epoxy resin/carbon fiber systems as reinforcing fillers, trying to profit from the chemical affinity between aromatics structures of GO/rGO and polar interactions with epoxy resin. GO/rGO was characterized by XPS, TGA was performed on carbon fiber, epoxy resins and composites obtained and SEM was utilized to observe composite samples in detail once mechanical tests were conducted. Composites experienced noticeable enhancements by employing Bisphenol Epoxy (BP) cured with methyl cyclohexane-1,2-dicarboxylic anhydride (MCHDA) as matrix and carbon fiber of 300 g/cm2 as reinforcement; Young’s modulus, rupture stress and elongation to failure increased almost twofold compared to non-modified composites by adding GO in the system and even superior boosts can be appreciated with rGO, which additionally improves the flexural stress from 14.6 to 30.1 GPa. Flexural behavior is affected by the presence of GO or rGO, but due to the 3D configuration achieved it is difficult to observe a clear influence of the chemical groups in filler particles.